2010
DOI: 10.1111/j.1600-6143.2010.03165.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold Machine Perfusion Versus Static Cold Storage of Kidneys Donated After Cardiac Death: A UK Multicenter Randomized Controlled Trial

Abstract: One third of deceased donor kidneys for transplantation in the UK are donated following cardiac death (DCD). Such kidneys have a high rate of delayed graft function (DGF) following transplantation. We conducted a multicenter, randomized controlled trial to determine whether kidney preservation using cold, pulsatile machine perfusion (MP) was superior to simple cold storage (CS) for DCD kidneys. One kidney from each DCD donor was randomly allocated to CS, the other to MP. A sequential trial design was used with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
185
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(195 citation statements)
references
References 22 publications
(8 reference statements)
5
185
4
1
Order By: Relevance
“…There were no differences in PNF, acute rejection, and 1-year graft survival rates between the two groups. Similar 1-year graft survival (93.3% vs. 97.8%) and renal function were reported by the randomized clinical trial performed in UK in 2010 [12]. Surprisingly, the study showed no differences in DGF rates between HMP and cold storage (58% vs. 56%) but the fact that some of the kidneys allocated to HMP were actually put on ice before effective pumping may somehow explain this unexpected finding.…”
Section: Journal Of Transplantation Technologies and Research Respectivsupporting
confidence: 39%
“…There were no differences in PNF, acute rejection, and 1-year graft survival rates between the two groups. Similar 1-year graft survival (93.3% vs. 97.8%) and renal function were reported by the randomized clinical trial performed in UK in 2010 [12]. Surprisingly, the study showed no differences in DGF rates between HMP and cold storage (58% vs. 56%) but the fact that some of the kidneys allocated to HMP were actually put on ice before effective pumping may somehow explain this unexpected finding.…”
Section: Journal Of Transplantation Technologies and Research Respectivsupporting
confidence: 39%
“…As data were not available for all patients some of the confidence intervals were wide, increasing the risk of a type 2 error. We also did not have data regarding delayed graft function which was related with machine perfusion parameters in some studies [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, Moers have stated later on that three years after transplantation machine perfusion MP had no advantage over cold storage in terms of graft survival in DCD kidney transplantation. In addition, a multicentre study conducted in the UK showed no advantage of machine perfusion MP over cold storage in terms of incidence of delayed graft function, renal function and 1 year graft and patient survival [15]. A meta-analysis also showed that machine perfusion decreased the incidence of delayed graft function compared to static cold storage but graft and patient survival at 1 year were similar [23].…”
Section: Discussionmentioning
confidence: 99%
“…Machine perfusion has been shown to be beneficial for ECD kidneys [88] , but the results from a United Kingdom based trial comparing machine perfusion with cold storage were equivocal [89] . The effect of machine perfusion on DCD kidneys may decrease DGF by up to 38% but has no effect on longterm function [6,90] .…”
Section: Kidney Preservation and Machine Perfusionmentioning
confidence: 99%